2020
DOI: 10.1093/ofid/ofaa240
|View full text |Cite
|
Sign up to set email alerts
|

Five-Day vs 10-Day Postexposure Chemoprophylaxis With Oseltamivir to Prevent Hospital Transmission of Influenza: A Noninferiority Randomized Open-Label Study

Abstract: Background The efficacy and optimal duration of post-exposure influenza prophylaxis with oseltamivir is undetermined in hospital settings where immediate separation from index cases is not feasible. Methods In an open-label non-inferiority randomized clinical trial in a single-center university hospital, the efficacy of 5-day versus 10-day post-exposure prophylaxis with oseltamivir was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…It needs to be emphasized, that PEP efficacy may depend on the study setting and the question of the difference between a household and a nosocomial contact needs to be recognised. Nevertheless, very high efficacy observed in our study is in line with the corresponding studies set in a hospital environment (97% in the study by Shinjoh, 99% in the study by Ishiguro, and 99% in the study by Lepen) and is generally higher than those observed in household settings 21 , 23 , 26 . It may be attributed to various factors, including patient’s better compliance, the duration of contact (which may be ceased with a transfer to another room or discharge from the hospital, which is not a routine procedure in the majotiry of household contacts), and the contact quality – contact among patients differs substantially from household contact.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It needs to be emphasized, that PEP efficacy may depend on the study setting and the question of the difference between a household and a nosocomial contact needs to be recognised. Nevertheless, very high efficacy observed in our study is in line with the corresponding studies set in a hospital environment (97% in the study by Shinjoh, 99% in the study by Ishiguro, and 99% in the study by Lepen) and is generally higher than those observed in household settings 21 , 23 , 26 . It may be attributed to various factors, including patient’s better compliance, the duration of contact (which may be ceased with a transfer to another room or discharge from the hospital, which is not a routine procedure in the majotiry of household contacts), and the contact quality – contact among patients differs substantially from household contact.…”
Section: Discussionsupporting
confidence: 91%
“…Although the majority of patients were adults, there was a pediatric subgroup (the exact number of children was not specified), which opened the discussion on a possibility of shortening the PEP in children, as well 21 . Similarly, the recent randomized trial from Slovenia aimed to verify the possibility of a shorter PEP regimen by allocating 222 adult patients into 5- or 10-day PEP group; the study confirmed high PEP efficacy with a noninferiority of a shorter PEP course compared to the longer one 26 . There have been no controlled studies which would directly compare differences in hospitalized pediatric population, although a protocol for a prospective, multi-center, single-arm trial has been published and to the best of our knowledge the study is being conducted 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Current guideline recommends PEP, with oral oseltamivir or inhaled zanamivir for 7 days, in individuals at very high risk of developing complications from influenza and are unvaccinated, or where vaccination is contraindicated as soon as possible (no later than 48 h) after household exposure to influenza; or to all exposed residents or patients regardless of influenza vaccination history during an influenza outbreak in a long-term care facility or hospital [1]. Studies are now suggesting an even shorter course of PEP in the hospital setting with a 3-day [87] or 5-day oseltamivir regimen [88] could still be effective if the close contacts could be or could not be immediately separated from the index cases respectively. The 3-day regimen is now undergoing a prospective, multicentre, single-arm trial on its efficacy [89].…”
Section: Use Of Antiviral Agents To Control the Spread Of Influenza I...mentioning
confidence: 99%